EFFECT OF DIFFERENT PLANT GEOMETRY AND NITROGEN LEVELS, INRELATION TO GROWTH CHARACTERS, YIELD AND ECONOMICS ON SWEET CORN (ZEA MAYS SACHHARATA L.) AT BASTAR PLATEAU ZONE - ASHWANI KUMAR THAKUR; DUSHYANT SINGH THAKUR; RAKESH KUMAR PATEL; ADIKANT PRADHAN; PRAFULL KUMAR4 (The Bioscan, 2015)
Field experiment was conducted during Rabi season of 2014 at the S G College of Agriculture and Research Station, Jagdalpur (Chhattisgarh). The soil was sandy loam in texture, low in organic carbon (0.48%). available N (185 kg ha-1), available phosphorus (20.9 kg ha-1) and medium in available potassium (186 kg ha-1) with soil reaction (pH 6.8). The experiment was laid out in split-plot design by keeping four plant geometry, viz. G1-(30 x 30 cm), G2-(50 x 30 cm),G3-(30 x 60 cm) and G4-(50 x 50 cm) as a main plot and four nitrogen levels i.e. N1- (50 kg ha-1), N2-(75 kg ha-1), N3-(100 kg ha-1) and N4-(125 kg ha-1) as a sub-plot plot and was replicated three times. Plant population (94415), plant height (169.78 cm) and LAI (5.04) was recorded significantly highest in treatment G1 (30 x 30 cm) followed by G2 (50 x 30 cm). Fresh kernel weight (32.75 g) recorded significantly higher under treatment G4 (50 x 50 cm) among all plant geometry but it was significantly at par with G3 (60 x 30 cm) and minimum weight was gained by G1 (30 x 30 cm). In case of weight of cob with and without cover (246.47g and 216.77 g), and weight of cobs ha-1 (18507 kg ha-1) was recorded significantly highest in treatment G4 (50 x 50 cm). Net income (Rs.172513) was recorded significantly highest in G1 (30 x 30). However, B: C ratio was recorded statistically similar result in all plant geometry but highest value was obtained with G1 (30 x 30 cm).In case of different nitrogen levels, N4 (125 kg N ha-1) was recorded significantly tallest plant height (178 cm), days to 50% flowering (51 DAS), No. of cobs ha-1 (84860) and LAI (5.35). Significantly highest fresh kernel weight (34.51 g), weight of cob with (256.77) and without cover (236.80), weight of cobs ha-1 (21504.28) and number of cobs ha-1 (84860) was recorded under N4 (125 kg ha-1) among all the nitrogen levels. Highest gross income (Rs. 212833), net income (Rs. 175418) and B: C ratio (4.60) was recorded significantly higher in N4 (125 kg ha-1).